2014
DOI: 10.3389/fnbeh.2014.00323
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Extinction of Human Avoidance Behavior: Attenuating Effect of Safety Signals and Associations with Anxiety Vulnerabilities

Abstract: While avoidance behavior is often an adaptive strategy, exaggerated avoidance can be detrimental and result in the development of psychopathologies, such as anxiety disorders. A large animal literature shows that the acquisition and extinction of avoidance behavior in rodents depends on individual differences (e.g., sex, strain) and might be modulated by the presence of environmental cues. However, there is a dearth of such reports in human literature, mainly due to the lack of adequate experimental paradigms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 60 publications
8
70
0
Order By: Relevance
“…Consistent with the current findings, females, in contrast, have been shown to display greater avoidance behavior (Sheynin, Moustafa, Beck, Servatius, & Myers, 2015). Using both human and animal models of avoidance behavior, previous work has shown that females are also slower to extinguish these avoidance behaviors than males (Beck, Jiao, Pang, & Servatius, 2010; Sheynin, Beck, Servatius, & Myers, 2014). There are several possible explanations that could account for these differences in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the current findings, females, in contrast, have been shown to display greater avoidance behavior (Sheynin, Moustafa, Beck, Servatius, & Myers, 2015). Using both human and animal models of avoidance behavior, previous work has shown that females are also slower to extinguish these avoidance behaviors than males (Beck, Jiao, Pang, & Servatius, 2010; Sheynin, Beck, Servatius, & Myers, 2014). There are several possible explanations that could account for these differences in behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could also test whether the addition of specific “safety signals” during therapy could attenuate the exaggerated avoidance behavior, as suggested by a recent study examining the effect of adding such “safety signals” to this task. 32 …”
Section: Discussionmentioning
confidence: 99%
“…To test avoidance behavior, subjects were administered a simple computer-based task recently developed by our group, 31, 32 and based on earlier work by Molet et al 30 On this task (Figure 1), subjects controlled a spaceship and were instructed to gain points by shooting and destroying an enemy spaceship that randomly appeared on the screen. Every 20 s, rectangles appeared for 5 s at the top of the screen (warning period).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations